Engineered hetero structured arrays of ZnO NanoX (X = discs, rods and wires) and CdTe quantum dots for advanced electron transport applications. (5th March 2018) - Anas, S.; Nair, P.V.; Mahesh, K.V.; Linsha, V.; Shuhailath, A.; Mohamed, A.P.; Warrier, K.G.K.; Ananthakumar, S.
Abstract: Novel hetero structured arrays of CdTe quantum dots capped ZnO nanostructures were successfully prepared through a three tier process. C-axis oriented ZnO nanostructures, namely ZnO nanox (where, x = discs, rods and wires), were prepared on glass and ITO substrates by employing simple, template free and low temperature solvothermal methods. CdTe quantum dots were synthesized subsequently through an organometallic route. ITO/ZnO NanoX/CdTe heterostructured arrays were finally developed, by capping ZnO nanostructured arrays with CdTe quantum dots by using 3-mercaptopropionic acid. The crystalline, structural, morphological and optical features of the individual nanostructures and the heterostructured arrays were investigated by using XRD, HR-TEM, SEM, EDAX, AFM, UV and PL. The role of solvents, solution concentration and temperature on deciding the final morphologies in solvothermal syntheses were studied and the possible growth mechanism of the different nanostructure arrays were proposed. The comparative electron transport studies of the ITO/ZnO NanoX/CdTe heterostructure arrays were carried out. Electrochromic display units having fast electron transport capabilities were developed. The study put forth many futuristic applications of these hetero structured assemblies in wide spectrum of scientific and industrial disciplines, particularly in the areas where a fast electron transport is required. Graphical abstract: Image 1 Highlights: Pure, single crystalline, C- axis oriented ZnO NanoX (X = discs, rods and wires) arrays are solvothermally synthesized. The morphologies of ZnO are varied with respect to the type of solvent, solution concentration and temperature. Novel, ITO/ZnO NanoX/CdTe hetero structured assemblies are developed by capping ZnO NanoX with CdTe QD's. Electron transport efficiencies of the assemblies descends in the order of ZnO array morphology as, wires > rods > discs. Hetero structured assemblies enable fast switching (< 1S under 2V) in electrochromic devices.